2019
DOI: 10.1002/lpor.201800287
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Tunable Distributed Feedback (DFB) Laser on Silicon

Abstract: An electronically tunable distributed feedback (DFB) laser heterogeneously integrated on a silicon photonics platform is experimentally demonstrated. Tuning is achieved through carrier injection into the tuning layer of a tunable twin‐guide III–V membrane on silicon. A 2 nm continuous tuning range is achieved with a single tuning current. Continuous‐wave single‐mode laser operation with a side‐mode suppression ratio larger than 44 dB across the tuning range is obtained. Measured wavelength switching times are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Most often, frequency tuning of integrated lasers relies on the thermo-optic (TO) effect 10 , which is relatively slow (kHz-level speed). And even while MHz-level frequency tuning can be achieved by current sweep of PN junctions of III-V or silicon waveguides, this carrier-induced effect produces unwanted intensity modulation 29 as well as additional loss that are not compatible with narrow linewidth lasers. As a result, currently in integrated photonics, frequency modulation of laser has to rely on a modulator that is external to the laser 30 34 or optical pumping 35 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Most often, frequency tuning of integrated lasers relies on the thermo-optic (TO) effect 10 , which is relatively slow (kHz-level speed). And even while MHz-level frequency tuning can be achieved by current sweep of PN junctions of III-V or silicon waveguides, this carrier-induced effect produces unwanted intensity modulation 29 as well as additional loss that are not compatible with narrow linewidth lasers. As a result, currently in integrated photonics, frequency modulation of laser has to rely on a modulator that is external to the laser 30 34 or optical pumping 35 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Most often, frequency tuning of integrated lasers relies on the thermo-optic (TO) effect [10], which is relatively slow (kHz-level speed). And even while MHz-level frequency tuning can be achieved by current sweep of PN junctions of III-V or silicon waveguides, this carrierinduced effect produces unwanted intensity modulation [27] as well as additional loss that are not compatible with narrow linewidth lasers . This limitation is more severe at short wavelength below silicon's bandgap wavelength, where currently only thermal tuning can be used for external cavities of integrated lasers.…”
Section: Introductionmentioning
confidence: 99%
“…In other work, researchers have also altered the ambient temperature [ 29 ] and medium [ 34 ] to affect the laser emission. In addition, some researchers have shown that electronically tunable distributed feedback (DFB) lasers can be achieved through electroactive dielectric elastomer actuators [ 35 ] and III–V InGaAsP tuning layers [ 36 ]. To date, there have been a few studies on WGM electrical tuning; microstructural fibers based on dual-frequency liquid crystal (DFLCs) [ 37 ] and metal-dielectric core–shell hybrid microcavities with thermo-optical effects [ 38 ] provide WGM tuning schemes for wavelength shifting by applied electric fields.…”
Section: Introductionmentioning
confidence: 99%